Pro Tools for music production : recording, editing and mixing - Collins, Mike, 1949- (Focal, 2004)
Pro Tools for Music Production is a definitive guide to the system for new and professional users. Extensively illustrated in colour and packed with time saving hints and tips, you will want to keep to hand as a constant source of information. The book takes a real-world approach and shows how to build the right system to suit your needs. Detailed chapters on recording, editing and mixing blend essential knowledge with tutorials and practical examples from actual recordings. The second edition features a wealth of new and updated material.